A Comparative Study of Sublingual Misoprostol and Manual Vacuum Aspiration for Incomplete Abortion Treatment - Shabnam, Bushra Bashir, Zaib Un Nisa, Amna Baloch, Khizera Anwar, Nighat Afridi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this analysis is to do the comparison of sublingual misoprostol and manual vacuum aspiration for the incomplete abortion treatment. Study Design: Randomized/Control Trial Place and Duration: Department of Gynecology and Obstetrics of Combined Military Hospital, Peshawar from January 2021 to December 2021. Methods: There were 108 women with ages 18-50 years were presented in this study. All the included women had incomplete abortion. Age, BMI, gestational age, and parity were among the specific demographics of the recruited cases that were documented after receiving written, informed consent. 54 females received sublingual misoprostol (600mg) in group I and 54 patients of group II manual vacuum aspiration. Post-treatment outcomes among both groups were assessed in terms of decreased hemoglobin, side effects, abortion completion and satisfaction rate by using visual analogue scale. SPSS 24.0 was used to analyze all data. Results: Among 108 females, 35 (32.4%) patients had age 18-30 years, 55 (50.9%) had age 31-40 years and 18 (16.7%) had age >40 years. 60 (55.6%) had BMI <25kg/m2 and 48 (44.4%) had BMI >25kg/m2. Mean parity of the females were 2.04±3.19 and mean gestational age was 13.4±8.61 weeks. In group I hemoglobin level <1 g/dl was lower found in 27 (50%) cases as compared to group I in 35 (64.8%) cases. Frequency of side effects in group I was higher 38 (70.4%) as compared to group II 22 (40.7%) with p value 0.006. Frequency of complete abortion in group II was higher in 50 (92.6%) as compared to group I 39 (72.2%) with (p<0.003). Satisfaction rate was higher in manual vacuum aspiration group as compared to sublingual misoprostol group. Conclusion: This study exhibited that MVA was effective and satisfactory among patients of incomplete abortions in terms of decreased hemoglobin level, less side effects and higher number of complete abortions. Keywords: Incomplete abortion, Hemoglobin level, Side Effects, Complete Abortion